An empirical analysis of control activities in managing risk for sustainable Malaysian manufacturing SMES / Nor Hafizah Abdul Rahman ...[et al.] - Abdul Rahman, Nor Hafizah; Ghani, Erlane K.; Hamzah, Noradiva; Aziz, Khairul Azman (Universiti Teknologi MARA Cawangan Selangor, 2017)
This study presents an empirical analysis of control activities among Malaysian manufacturing SMEs in managing the risk of employee fraud for the sustainability of SMEs. Continuous measurement, monitoring and evaluation of control activities are regarded as the basis to form effective controls against employee fraud. This study is based on an in-depth case study that examined how an organisation forms a good foundation of control activities to curb employee fraud in SMEs. Semi-structured interviews were conducted with the owner of three manufacturing SMEs from the Food and Beverage industry. This study identifies and summarises the current control activities based on (1) response to objectives risks, (2) design of appropriate types of control activities at various levels, and (3) segregation of duties. The result shows that most of the manufacturing SMEs implement control activities partially automated through the entity's information technology system. This study provides a basis for several aspects of future research on other components of internal control by integrating each component in assessing business risks and explanation towards SME sustainability.